1996
DOI: 10.1111/j.1365-246x.1996.tb00022.x
|View full text |Cite
|
Sign up to set email alerts
|

Topographic Core-Mantle Coupling and Polar Motion On Decadal Time-Scales

Abstract: S U M M A R YAssociated with non-steady magnetohydrodynamic (MHD) flow in the liquid metallic core of the Earth, with typical relative speeds of a fraction of a millimetre per second, are fluctuations in dynamic pressure of about lo3 N m-2. Acting on the non-spherical core-mantle boundary (CMB), these pressure fluctuations give rise to a fluctuating net topographic torque L i ( t ) (i = 1 , 2 , 3 t w h e r e t denotes time--on the overlying solid mantle. Geophysicists now accept the proposal by one of us (RH) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 41 publications
0
19
0
Order By: Relevance
“…Electromagnetic core± mantle coupling is too small because the electrical conductivity of the lower mantle is too low (e.g. Recent investigations show that the topographic coupling is probably too small by a factor 10 (Greff- Lefftz & Legros 1995) or 5 (Hide et al 1996) to explain the decadal variations of polar motion. Holme 1998a,b).…”
Section: Introductionmentioning
confidence: 99%
“…Electromagnetic core± mantle coupling is too small because the electrical conductivity of the lower mantle is too low (e.g. Recent investigations show that the topographic coupling is probably too small by a factor 10 (Greff- Lefftz & Legros 1995) or 5 (Hide et al 1996) to explain the decadal variations of polar motion. Holme 1998a,b).…”
Section: Introductionmentioning
confidence: 99%
“…Topographic core-mantle coupling has been considered a possibility, but this means of excitation is unable to reproduce the observed polarization or period, and its magnitude is too small to drive the wobble by a factor of 5 [Hide et al, 1996].…”
mentioning
confidence: 99%
“…Interactions between the fluid outer core and mantle also appear to be ineffective in exciting decadal polar motion variations. Electromagnetic coupling between the core and mantle appears to be 2–3 orders of magnitude too weak [ Greff‐Lefftz and Legros , 1995] and topographic coupling appears to be too weak by a factor of three to ten [ Greff‐Lefftz and Legros , 1995; Hide et al , 1996; Hulot et al , 1996]. In addition, the modeled decadal polar motion variations resulting from these studies show little agreement in phase with the observed variations.…”
Section: Discussion and Summarymentioning
confidence: 99%